Evaluation of chemical and nutritional quality attributes of selected mango varieties at three stages of ripeness, grown in lower Eastern province of Kenya – part 2 - Okoth, E.M.; Sila, D.N.; Onyango, C. A.; Owino, W.O.; Musyimi, S.M.; Mathooko, Francis M. (My University, 2013)
Mango fruits are widely grown in Kenya for domestic and export utilization. Selected chemical and nutritive quality attributes of Apple, Ngowe and Kent were evaluated at three stages of ripeness. The cultivars were obtained at the unripe stage from Lower Eastern Province (Kitui and Machakos) of Kenya. Total titratable acidity (TTA), vitamin C, and crude fiber decreased with ripeness, whereas total soluble solids (TSS), TSS/TTA, β- carotene, crude fat, crude protein, fructose, glucose, and sucrose increased with increasing ripeness. The Apple varieties showed superior quality attributes in terms of low TTA of 0.04%, higher TSS of ≥19.50 ºBrix at ripe stage. It registered the highest vitamin C content of 109.35mg/100g (FW) at the unripe stage, lowest moisture content of 79.96% and highest dry matter of 20.04% both at their ripe stages. It also recorded the highest crude fiber content (0.89%) at its unripe stage and had highest crude fat content (0.11%) at its ripe stage compared to other varieties at the same stages of ripeness. The Kent varieties scored lowest in TSS (6.50ºBrix), vitamin C content at all stages, moderately high moisture content and lowest dry matter at their intermediate stage, lowest crude protein at unripe stage, and lowest in fructose of 8.54 mg/ml. Kent variety fromKitui zone also scored poorly in TSS/TTA ratio of 16.67 and had the lowest content in β-carotene at their unripe stage. It had the highest moisture content of 86.32% and the least dry matter of 13.68%. This variety also had low content of crude protein at their unripe stage of 0.02%. Ngowe fruit from the two zones scored moderately at the three stages of ripeness on most of the attributes evaluated. The results indicated that Apple mango variety is the most promising for both fresh consumption and processing purposes as it scored highly in most of the chemical and nutritional quality attributes analyzed.